OP0095 Prediction of connective tissue disease in an at-risk cohort using a novel interferon stimulated gene expression score. (15th June 2017) - Yusof, MY Md; El-Sherbiny, Y; Psarras, A; Hensor, E; Alase, A; Mohamed, A; Wittmann, M; Emery, P; Vital, EM
Abstract : Background: A period of ANA positivity and other immune dysregulation precedes connective tissue disease, providing a potential opportunity for disease prevention. Type I interferons (IFN-I) play a role in pathogenesis but their role in disease initiation is unclear. Objectives: To develop biomarkers of progression to systemic autoimmunity, with a view to enabling early intervention for disease prevention. Methods: A prospective observational study was conducted in 125 patients At Risk of CTD defined by (i) ANA; (ii) ≤1 clinical SLE criteria; (iii) symptom duration <12 months and (iv) treatment-naïve. Progression was defined by meeting 2012 ACR/SLICC SLE, 2016 ACR/EULAR Primary Sjogren's, or other diagnostic criteria. Expression of 30 selected="selected" ISGs was measured using Taqman. Factor analysis was used to reduce the gene expression data to a limited set of factors, which were compared between patient groups using Mann Whitney U Test. Two factor scores explained 80% of the data variance; "Score A" (composed of IFN-α responsive genes) and "Score B" (genes responsive to IFN-α and γ). 95 healthy controls and 107 SLE patients were used as negative and positive controls. Results: 82 patients with 1-year follow-up data were studied. 71 were female with mean age 48±15 years. 16 (20%) patients progressed to CTD (SLE=12, Sjogren's=4) in the following 12 months. At baseline, only IFN Score A was increased in both At Risk-CTD and SLE vs healthy controls; p<0.001. IFN Score B was only increased in true established SLE. In At-Risk patients, IFN Score B was low in patients who did not progress and increased in those who did progress; p=0.004. However, there was no difference in IFN Score A between these two groups; p=0.252 (Figure 1 ). Although complement levels and lymphocyte counts were lower in SLE, these were not different between the At-Risk progression and non-progression groups. Anti-dsDNA titres were higher in SLE but not different between the progression groups; all p>0.10. Conclusions: A novel ISG score predicts progression from ANA+ to clinical autoimmune disease. This may allow early intervention to prevent CTD. Analysis of other clinical, immunological and imaging biomarkers are in progress as well as a validation cohort. Disclosure of Interest: M. Y. Md Yusof: None declared, Y. El-Sherbiny Grant/research support from: AstraZeneca, A. Psarras: None declared, E. Hensor: None declared, A. Alase: None declared, A. Mohamed: None declared, M. Wittmann: None declared, P. Emery Grant/research support from: AstraZeneca, E. Vital Grant/research support from: AstraZeneca